2016
DOI: 10.1039/c6sc00771f
|View full text |Cite
|
Sign up to set email alerts
|

Flavoenzyme CrmK-mediated substrate recycling in caerulomycin biosynthesis

Abstract: Biochemical and structural investigations into the flavoenzyme CrmK reveal a substrate recycling/salvaging mechanism in caerulomycin biosynthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…2). The cam contains 20 ORFs including essential dipyridine ring biosynthetic genes and backbone post-modification genes [22,25,[27][28][29] (Fig. 2 and Table S7), which indicates that Actinoalloteichus sp.…”
Section: Genomic Analysis Of the Crm A Biosynthetic Potential In Actimentioning
confidence: 99%
See 1 more Smart Citation
“…2). The cam contains 20 ORFs including essential dipyridine ring biosynthetic genes and backbone post-modification genes [22,25,[27][28][29] (Fig. 2 and Table S7), which indicates that Actinoalloteichus sp.…”
Section: Genomic Analysis Of the Crm A Biosynthetic Potential In Actimentioning
confidence: 99%
“…Then, the 2, 2'-dipyridine ring is finally converted into the CRM A by a series of post-modification reactions, including aminohydrolysis, oxime formation and methylation [22,[26][27][28][29]. CRM A can induce the generation of regulatory T cells to avoid T cell responses and change the function of B cells, which significantly inhibits the Mixed Lymphocyte Reaction (MLR) [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…2). The cam contains 20 ORFs including essential dipyridine ring biosynthetic genes and backbone post-modi cation genes [23,26,[28][29][30] (Fig. 2 and Table S4), which indicates that Actinoalloteichus sp.…”
Section: Genomic Analysis Of the Crm A Biosynthetic Potential In Actimentioning
confidence: 99%
“…This new metabolic engineering strategy named as cofactor engineering has been well applied to microbial second metabolites development [39][40][41]. Previous study had revealed that the biosynthesis of CRM A required several essential avoenzymes, including CamD, which completed the formation of the picolinic acid precursor; CamH, which catalyzed the formation of the oxime group, and CamK, which maintained the substrate recycling process [23,28,29]. Thus, enhancing the intracellular ribo avin supplement could facilitate the formation of these avoenzymes, which may accelerate CRM A production in turn.…”
Section: Enhancement Of Crm a Production By Uv Mutagenesismentioning
confidence: 99%
See 1 more Smart Citation